Comparison of the Postoperative Pain Following Endodontic Irrigation Using 1.3% Versus 5.25% Sodium Hypochlorite in Mandibular Molars with Necrotic Pulps: Postoperative Pain in Mandibular Molars - Rahim, Ekta; Memon, Mahwish; Memon, Parveen; Parveen, Sunaila; Qureshi, Azizullah Muhammad Nawaz; Shaikh, Abdul Ghani (Pakistan Journal of Health Sciences, 2024)
Endodontic irrigation plays a crucial role in root canal treatment, aiming to disinfect the root canal system be removing debris, bacteria and tissue remnants. Objective: To compare the postoperative pain between two concentrations (1.3% and 5.25%) of irrigation using sodium hypochlorite (NaOCl) in lower molars with necrotic pulps. Methods: Sixty patients with nonvital pulps in mandibular molars, either gender, mature teeth with a closed apex or age between 18 and 60 years were included. Patients were assessed for postoperative pain in each group at 24 hours. The Chi-square test and student t-test were used to compare the postoperative pain outcome of both groups. Results: The mean age of the patients in group A was 33.76 ± 4.06 years, and in group B was 32.10 ± 5.84 years. Pre-operative pain was statistically insignificant in both groups (p = 0.123), with an average VAS of 3.16 ± 0.64 in group A and 3.40 ± 0.49 in group B. The average pain was significantly lower at 1.33 ± 0.47 in the 1.3% sodium hypochlorite group compared to 1.63 ± 0.66 in the 5.25% NaOCl group (p = 0.051) after 24 hours. The average post-operative pain score was significantly higher in females compared to males in the 1.3% NaOCl group (p = 0.033). However, the average post-operative pain score was statistically insignificant between males and females in the 5.25% NaOCl group (p = 0.445). Conclusion: Endodontic irrigation using 1.3% NaOCl was found to be more effective in reducing post-operative pain compared to endodontic irrigation using 5.25% NaOCl.